Cultural belonging and disability. For a multidimensional reading of double diversity in educational and social contexts - Emanuela Bini (University of Bologna, 2020)
In Italy the increasing number of disabled migrant students suggests to renew welcoming strategies in order to build educational projects and the path of inclusion which also concerns migrant families. Disabled migrant children represent an educational and social challenge that invites to reflect about the importance of culture in educational activities, in the relationship with families and in the social networking to support the most vulnerable families. This article, based on a review of the main studies, provides a multidimensional reading about double diversity in educational and social contexts in order to describe the complexity of the subject and to define proper inclusive actions.